Ruptured aneurysm of abdominal aorta: is surgery the best treatment? - Freire, Artur Dantas; Carvalho, Aline Vasconcelos de; Xavier, Clara Rafael Silva; Medeiros, Lucas de Farias Farros; Rêgo, Amália Cinthia Menezes; Araújo-Filho, Irami (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2016)
Objective: The aim of this article is to compare the procedures used in the treatment of ruptured abdominal aortic aneurism, in order to determine the best approach to this urgency. Methods: The rupture of abdominal aortic aneurysm is a serious complication, with high mortality rate. Early surgery is related to great survival of these patients. However, there are two methods of treatment (open and endovascular surgery). The present study is a review of the literature in PubMed, UpToDate, Scopus and Scielo databases, using the key words "aneurysm, aortic aneurysm, abdominal aorta", "rupture", "aortic surgery”, “endovascular procedure", "angioplasty", "endoluminal repair", “percutaneous transluminal angioplasty”. We included English and Portuguese language articles, published between 2006 and 2015, addressing the treatment of the ruptured aneurysm of abdominal aorta. Conclusion: Significant differences in the mortality rates of open surgery compared to the endovascular treatment of ruptured aneurysm definitely have not been demonstrated. There is some evidence that perioperative (30 days) results after endovascular aneurysm correction of ruptured aneurism can be better than open repair.